NILAI DALAM SOSIAL TRADISI PERANG OBOR DAN RELEVANSINYA TERHADAP PEMBELAJARAN IPS SEKOLAH DASAR - Nur Kumala Reza Damayanti; Erik Aditia Ismaya; Wawan Shokib Rondli (STKIP Pesisir Selatan, 2026)
Social studies (IPS) learning at Muhammadiyah Kriyan Elementary School is still dominated by conventional textbook-based methods that rarely draw on local wisdom, causing low student engagement and shallow understanding of social values; national data show 74.2% of young Indonesians identify more with global popular culture than local traditions, and over 70% of teachers still rely solely on textbooks (BPS, 2023; Sofyan et al., 2025). This study identifies the social values in the Torch War Tradition of Tegalsambi Village and analyzes their relevance to elementary IPS learning. A qualitative case study approach was used, with data collected through observation, interviews, and documentation, analyzed via data reduction, data display, and conclusion drawing, with trustworthiness established through credibility, transferability, dependability, and confirmability. Results show the tradition embodies five core social values—mutual cooperation, togetherness and solidarity, tolerance, social awareness, and religiousness—internalized through family socialization, community socialization, and annual ritualization. These values are strongly relevant to IPS learning across cognitive, affective, and psychomotor domains, particularly for socio-cultural diversity, cooperation, and social interaction, and can be integrated through three models: story-based learning, field trips, and simple projects. Teachers thus need to integrate local wisdom into IPS instruction to strengthen engagement, motivation, and character formation.